EVALUATION OF EFFICIENCY OF THE TRUST TECHNIQUE AND THE MULLIGAN CONCEPT of ARTICULAR CORRECTION AT OSTEOCHONDROSIS OF THE THORACIC SPINE - Николайчук, Ольга; Перепелица, Олеся; Доцюка, Лидия; Голунга, Марьян (SWorldJournal, 2020)
The manual therapy is recognized among the professionals as the most efficient method of the decompensatory influence on the human spinal motion segment. The relevance of this investigation is based on the selection of the most effective manual therapy me